Targeting HPV16 DNA using CRISPR/Cas inhibits anal cancer growth in vivo. (7th July 2018) - Hsu, David S; Kornepati, Anand VR; Glover, Wayne; Kennedy, Edward M; Cullen, Bryan R
Aim: The goal of this study was to determine if a single AAV vector, encoding Cas9 and guide RNAs specific for the HPV16 E6 and E7 genes, could inhibit the growth of an HPV16-induced tumor in vivo .Materials & methods: We grew HPV16 +, patient-derived anal cancer explants in immunodeficient mice and then challenged these by injection of AAV-based vectors encoding Cas9 and control or HPV16-specific guide RNAs.Results & conclusion: We observed a significant and selective reduction in tumor growth when the HPV16 E6 and E7 genes were targeted using Cas9. These studies provide proof of principle for the hypothesis that CRISPR/Cas has the potential to be used to selectively treat HPV-induced tumors in humans.